The necessity of cell banks - A. G. Menzorov; O. L. Serov (Вавиловский журнал генетики и селекции, 2017)
Current progress in cell biology is connected with the development of somatic cell reprogramming technology. As a result of this technology, it is possible to produce induced pluripotent stem cells (iPSCs) from human somatic cells, for instance, from skin cells. As well as embryonic stem cells, these iPSCs possess pluripotency. Production of iPSCs opened new horizons for patient-specific cell therapy. Many researchers consider iPSCs a real basis for future regenerative medicine. Production of a patient’s iPSCs, their differentiation into somatic cells, and subsequent transplantation to a patient would allow them to avoid immunological rejection. In addition, a recently developed technology of directed genome modification, CRISPR/Cas, allows correction of genetic mutations in iPSCs. Thus, genetic mutations could be corrected in vitro, and after differentiation into a desired cell type, these cells could be transplanted to a patient. In addition, CRISPR/Cas could be used to introduce practically any mutations into iPSCs for the creation of disease-specific model cell lines that would facilitate disease mechanism studies and pharmaceutical drug testing. It is possible to turn off any gene or genes as well as to insert a genetic construct into a selected genomic region to temporarily turn on and off genes and remove chromosomal regions. Cell banks that are open to general use are necessary for efficient usage of iPSCs in biomedical research. Currently, there are no pluripotent stem cell lines in Russian Federation cell banks. Moreover, it is essential to develop standardized practice of culture and storage of that cell type. This mini-review focuses on the necessity of the creation of a pluripotent stem cell bank in the Russian Federation, a detailed description, and a recommended protocol for cell line deposition and usage.